(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic has substantially affected human society, from health care to economic structures, social relationships and environmental care. The objective of the present study was to evaluate how the pandemic caused by COVID-19 impacted on environmental changes in the Amazon scenario. This is an integrative review research carried out in August 2022 through an advanced search in the Science Direct database. For the selection of articles on that platform, the following descriptors were used: “COVID-19”, “Environmental changes” and “Amazon”. The research inclusion criteria were: research articles, excluding review articles, book chapters and other productions that were not part of the research articles category; open access articles published in the last year (2021-2022); and works that fall within the areas of “Environmental Science” and “Agrarian and Biological Sciences”. 04 articles were selected, based on the applied methodology, which demonstrated that the weakening of environmental inspection is one of the consequences of the pandemic period with several controversial actions of the Ministry of the Environment of Brazil that negatively impacted the environmental protection of the Amazon forest. In addition, traditional and indigenous peoples in the region have suffered from an increase in illegal miners invading indigenous lands and increasing exposure of these peoples to COVID-19. All this opens the way for further deforestation and degradation of forest biodiversity, and further research is needed to understand the real impact of the COVID-19 pandemic on the Amazon.